UNVIABLE WORLDS, DELIGHTFUL LIVES: APPROACHES BETWEEN LEILA DANSIGER AND BERNA REALE - Sarmento-Pantoja, Tânia [UNESP] (Universidade Federal do Para, 2023)
The article presents a study of Palomo (2012), by Berna Reale, a performance carried out in the streets of Belém and available in video and photographic series of the same name. It also analyzes the series Perigosos, subversivos, seditiosos (2018), subtitled Cadernos do povo brasileiro, by Leila Danzinger, which is part of the exhibition Hiatus: a ditatorial violence in Latin America, held at the Memorial da Resistência / Estação Pinacoteca, in São Paulo. Reale moves through the categories of shock and silence to reflect on the constitution of power, through an updated and subversive reading of the figuration of the knight and his horse, as an allegorical representation of state violence. Danzinger collects, takes up and reinstates a collection of books censored by the Civil and Military Dictatorship of 1964 superimposed on a series of photographs of political disappearances within that same dictatorship. What unites the two artists? Undoubtedly violence, especially that emanating from the State and the great issue of responsibility.
MUNDOS INVIABLES, VIDAS DELETABLES: APROXIMACIONES ENTRE LEILA DANSIGER Y BERNA REALE
Keywords: Berna; Dictatorship; Ethics; Leila Dazinger; Violence